Estrategias didácticas aplicadas a la lectoescritura para mejorar el rendimiento académico de los estudiantes del segundo año de Educación Básica Elemental de la Unidad Educativa Marco Aurelio Subía Batalla de Panupalí, 2021. - Madril Quishpe, Cecilia Karina (2022)
The research is oriented towards the use of didactic strategies that can be applied to reading and writing in order to improve the academic performance of students in the second year of elementary basic education. In this sense, it is considered that in Ecuador there is still little interest in the development of oral and written expression in children, as well as the presence of socio-economic, demographic, political and cultural factors that have an influence. Therefore, the objective is: To determine the effectiveness of didactic strategies applied to reading and writing in order to improve the performance of students in the second year of Elementary Basic Education at the "Unidad Educativa Marco Aurelio Subía Martínez Batalla de Panupalí", 2021. The work is based on the approaches of the mixed approach, under a deductive method. The observation technique is used with the observation guide instrument and the survey with its questionnaire instrument. The main result is that the didactic strategies applied to reading and writing are more interactive pedagogical alternatives that motivate students in the second year of elementary basic education, thus establishing a different way of teaching the basic principles of reading and writing and that students learn by reaching the achievements and goals proposed in the curricular plans.